TRANSLATION THROUGH ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND RISKS - Nuraliyeva Sarvinoz Hamraqulovna; Nurmuhammadiyeva Asila Ulugbekovna (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
In recent years, artificial intelligence (AI) has revolutionized the field of translation, transforming how languages are interpreted, processed, and communicated. Machine translation systems such as Google Translate, DeepL, and ChatGPT-based translators have significantly increased the accessibility of multilingual communication. This study explores both the opportunities and risks associated with AI-assisted translation from a linguistic and philological perspective. On one hand, AI offers unprecedented efficiency, speed, and inclusivity, enabling real-time translation across hundreds of languages and dialects. It also contributes to linguistic preservation by supporting low-resource languages and dialects that were previously marginalized. On the other hand, the increasing reliance on AI translation introduces serious challenges: semantic distortion, cultural loss, and ethical concerns about authorship and accuracy. This paper investigates how AI translation systems process syntax, semantics, and pragmatics, highlighting their dependence on massive data sets and neural network models. It also evaluates how bias and insufficient cultural knowledge can lead to mistranslations that distort meaning or perpetuate stereotypes. Through comparative analysis between human and machine translation, this research identifies the areas where AI excels—such as speed and pattern recognition—and where it fails—such as contextual interpretation, idiomatic nuance, and cultural sensitivity. The study concludes that while AI-assisted translation represents a major advancement in global communication, it cannot replace the human interpreter’s cultural and emotional understanding. Instead, AI should be viewed as a complementary tool within the translation ecosystem. Balancing efficiency with linguistic integrity is essential to ensure that technological innovation supports rather than undermines linguistic diversity and cultural authenticity.